Clinical studies on the use of antibiotic- and antiseptic-bonded catheters to prevent catheter-related infection - Bach, Alfons (Zentralblatt für Bakteriologie, 1995)
Central venous catheter-related infections are common despite adherence to hygienic guidelines for insertion and maintenance of these devices. It has been suggested that coating of intravascular catheters with antimicrobial agents, either antibiotics or antiseptics, could reduce the incidence of catheter-related infections. Recent studies have demonstrated the efficacy of antibiotic-coated and antiseptic-impregnated catheters in reducing bacterial colonisation and infection. Preliminary results of pilot studies indicate that silver impregnation of intravascular catheters may be effective. At present, these antimicrobial-bonded catheters seem to be an important addition to the choice of preventive strategies, but their definitive role and possible disadvantages such as induction of resistance still have to be clearly delineated.
Elektronische Reproduktion der Druck-Ausgabe 8. November 2011
Gesehen am 28.11.2023